The first Malayan Chinese women barristers and their pursuit of legal education in Britain, 1923–1934. (3rd July 2021) - Chen, Li
ABSTRACT : With the enactment of the Sex Disqualification (Removal) Act in 1919, the gender barrier was torn down and the once male-exclusive legal profession in the UK finally opened its doors to women. This article focuses upon its early Chinese beneficiaries, and traces the pioneer Chinese women students' odyssey to seek legal education at the Inns of Court in London and the University College London in the early 1920s and 1930s. It evaluates their performances at the Bar Examination and at the law school, and further explores the challenges they faced as they beat a path into the highly selective and traditionally male-dominated legal profession. Finally, it seeks to show how these Chinese women barristers were able to wield the legal knowledge and the advocacy skills obtained through their legal education to make notable contributions on returning home. However, their educational and professional success also reveals the persistence of gender and racial hierarchies across the empire despite ongoing legal reform and social activism, as they were subjected to confrontations and discriminations throughout their career.